PsycEXTRA Dataset 2012
DOI: 10.1037/e579192013-142
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ultrasound screening: False positive soft markers may alter maternal representations and mother-infant interaction

Abstract: Background: In up to 5% of pregnancies, ultrasound screening detects a ''soft marker'' (SM) that places the foetus at risk for a severe abnormality. In most cases, prenatal diagnostic work-up rules out a severe defect. We aimed to study the effects of false positive SM on maternal emotional status, maternal representations of the infant, and mother-infant interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…Information is also important because despite results from an invasive test ruling out chromosomal aberrations after the detection of soft markers, women's concerns about the baby's health are common and can be persistent . Lingering feelings of uncertainty about the significance of the marker detected , and increased maternal anxiety and depressive symptoms have been observed up to 2 months postpartum . Professionals also need to consider the partner's role in this situation, given women's desire to have a joint responsibility in making decisions about fetal diagnostics, including the partners' specific supportive role in such stressful situations .…”
Section: Discussionmentioning
confidence: 99%
“…Information is also important because despite results from an invasive test ruling out chromosomal aberrations after the detection of soft markers, women's concerns about the baby's health are common and can be persistent . Lingering feelings of uncertainty about the significance of the marker detected , and increased maternal anxiety and depressive symptoms have been observed up to 2 months postpartum . Professionals also need to consider the partner's role in this situation, given women's desire to have a joint responsibility in making decisions about fetal diagnostics, including the partners' specific supportive role in such stressful situations .…”
Section: Discussionmentioning
confidence: 99%
“…A baby with a major illness or a specific problem causes parents to lose their image of an ideal baby and begin to mourn . Viaux‐Savelon and colleagues showed that false‐positive ultrasound soft markers increase the anxiety level of mothers and alter maternal representations and mother–infant interactions in a negative way . Consequently, it could be thought that ARM increases anxiety because of disturbances in maternal representations as well as physical difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments, they demonstrated expectancies for synchronized and contingent exchanges with the social partner (here the mother), since two months old. The key role of synchrony was also found at early age in more natural early interaction such as home breast feeding (Viaux-Savelon et al, 2012). In (Saint-Georges et al, 2011), we investigated early signs of autism by modeling child's development with an interpersonal synchrony point of view.…”
Section: Non-verbal Evidence Of Interpersonal Synchronymentioning
confidence: 99%